COMPARAÇÃO INTERNACIONAL ENTRE CUSTOS UNIVERSITÁRIOS - Thiago Coelho Soares (Universidade Federal de Santa Catarina, 2011)
This article is, objectively, in a comparative analysis of cost per student between universities in different countries. However, we attempted to collect information related to this issue. To this end, we conducted interviews with personalities that could clarify this issue. The results show the importance of observing carefully the differences in international higher education. This time, an adaptation of the Brazilian system to the European or American would be important. Therefore, we concluded that international comparisons should meet at least two basic factors: purchasing power in the country and level of research at the university. Thus, international comparisons between the universities will be less distorted, which will facilitate business prospects.